Systematic comparative study of computational methods for T-cell receptor sequencing data analysis - Afzal, Saira; Gil-Fariña, Irene; Gabriel, Richard; Kalle, Christof von; Schmidt, Manfred; Fronza, Raffaele (Briefings in bioinformatics, 2019)
Abstract. High-throughput sequencing technologies have exposed the possibilities for the in-depth evaluation of T-cell receptor (TCR) repertoires. These studie